The Effect of Net Income, Price-To-Book Value, and Price-Earnings Ratio on Stock Prices in The Food and Beverage Industry Listed on The Indonesian Stock Exchange Period 2016-2020 - Maria, Theodora Inda; Putri, Hana Tamara; Iskandar, Fadil (International Conference on Business Management and Accounting, 2025)
The purpose of this study is to analyze the effect of market ratios (independent variables: Net Profit, Price to Book Value, Price Earnings Ratio on variables bound to stock prices) simultaneously and personally on the food and beverage industry in Indonesia Stock Exchange for the period 2016-2020. The data analysis method used in this study is a quantitative descriptive method with multiple linear regression analysis tools that are useful for seeing the relationship between independent variables and dependent variables. The program used to process this research data is SPSS version 22. The tests carried out are the F hypothesis test, t hypothesis, and coefficient of determination (R2). This industrial estate is a company whose activities are engaged in food and beverages for the needs of the community. Companies listed on the Indonesia Stock Exchange are PT Delta Djakarta Tbk (DLTA), PT Indofood CBP Makmur Tbk (ICBP), PT Indofood Sukses Makmur Tbk (INDF), PT Mayora Indah Tbk (MYOR), PT Multi Bintang Indonesia Tbk (MLBI), PT Nippon Indosari Corporindo Tbk (ROTI), PT Prasidha Aneka Niaga Tbk (PSDN), PT. Sekar Bumi Tbk (SKBM), PT Sekar Laut Tbk (SKLT), PT Siantar Top Tbk (STTP), PT Tiga Pilar Sejahtera Food Tbk (AISA), PT Tri Banyan Tirta Tbk (ALTO), PT Ultra Jaya Industri Tbk (ULTJ), PT Wilmar Cahaya Indonesia Tbk (CEKA). Based on the results of this study, net profit, price-to-book value, and price-earner ratio have a significant effect on stock price simultaneously. At the same time, it is known that there is a significant influence between net profit and stock prices in the food industry listed on the Indonesia Stock Exchange for the 2016-2020 period. Price-to-book value does not have a significant effect on stock price in personal, while price-earnings ratio has a significant effect on the stock price.